The Oxford handbook of identities in organizations - Brown, Andrew, 1964- (Oxford : Oxford University Press, 2020)
Conceived as the meanings that individuals attach to their selves, a substantial stockpile of identities-related theorizing, accumulated across the arts, social sciences and humanities over many decades, continues to nourish contemporary research on self-identities in organizations. This handbook offers a comprehensive assessment of current debates and major theories in research on identities in organizations. It provides an interdisciplinary review of the processes of identity construction, how, why, and when such processes occur, and their implications for organizing and individual, group, and organizational outcomes.
The Killing Fields of Identity Politics / Caroline Clarke, David Knights -- Organization Sexualities and LGBTQ+ Identities / Nick Rumens -- Entrepreneurship and Identity / Emmanuelle Fauchart, Marc Gruber -- Emotions and Identity / Ingo Winkler -- Age Identity and Organizations: Critical Potential and Challenges / Susan Ainsworth -- Identities and Identification: Beyond our Fixation on the Organization / Blake E. Ashforth, Jordana R. Moser, Philipp Bubenzer -- Identity Regulation and Globalisation / Mehdi Boussebaa -- Theorizing the 'I' in Institutional Theory: Moving Forward Through Theoretical Fragmentation, not Integration / Jaco Lok -- Identity Saves the World? Musings on Where Identity Research Has Been and Where It Might Go / Michael G. Pratt -- 'Identity Work': A Metaphor Taken Literally / Rosie Oswick, Cliff Oswick -- Lacan, Identities and Organizations: Potentialities and Impossibilities / Kate Kenny -- Finding Ourselves in Space: Identity and Spatiality / Alison Hirst, Michael Humphreys -- Identities, Digital Nomads and Liquid Modernity / Sumati Ahuja, Natalia Nikolova, Stewart Clegg -- Performed Identities / Nic Beech, Stephen Broad -- A Psychodynamic Perspective on Identity as Fabrication / Gianpiero Petriglieri -- Anchored in the Past: Nostalgic Identities in Organizations / Yiannis Gabriel -- Historical Methods for Researching Identities in Organizations / Michael Rowlinson, Michael Heller -- The Liminal Playground: Identity Play and the Creative Potential of Liminal Experiences / Herminia Ibarra, Otilia Obodaru -- How can I study who you are? Comparing grounded theory and phenomenology as methodological approaches to identity work research / Michael J. Gill -- Identity Work in Developing Collaborative Leadership / Barbara Simpson, Brigid Carroll -- Paradoxes in the Pursuit of Positive Identities: Individuals in Organizations Becoming Their Best / Mathew L. Sheep --
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 31, 2020).
Keywords: Organizational behavior; Identity (Psychology); Organizational change